Impact of interseismic deformation on phase transformations and rock properties in subduction zones - Cionoiu, Sebastian; Moulas, Evangelos; Tajcmanová, Lucie (Scientific reports, 2019)
Phase transformations greatly affect physical properties of rocks and impose a first-order control on geodynamic processes. Under high deformation rates, rheological heterogeneities cause large spatial variations of stress in materials. Until now, the impact of higher deformation rates, rock heterogeneity and stress build up on phase transformations and material properties is not well understood. Here we show, that phase transitions are controlled by the stress build-up during fast deformation. In a deformation experiment (600 °C, 1.47 GPa), rock heterogeneity was simulated by a strong elliptical alumina inclusion in a weak calcite matrix. Under deformation rates comparable to slow earthquakes, calcite transformed locally to aragonite matching the distribution of maximum principal stresses and pressure (mean stress) from mechanical models. This first systematic investigation documents that phase transformations occur in a dynamic system during deformation. The ability of rocks to react during fast deformation rates may have serious consequences on rock rheology and thus provide unique information on the processes leading to giant ruptures in subduction zones.
Gesehen am 05.03.2020